The Psychological and Sleep-related Impact of Coronavirus Disease 2019 (COVID-19): A Systematic Review - Solehati, Tetti; Kosasih, Cecep Eli; Hermayanti, Yanti; Mediani, Henny Suzana (Kesmas, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has had a global impact on mental health and sleeps quality that is unprecedented in the 21st century.This systematic review aimed to assess the psychological impact of COVID-19 and its effect on people’s sleep. Systematic searches were conducted viaPubMed, ScienceDirect, and ProQuest from 2019 to August 2020, following PRISMA guidelines. Articles were selected based on eligibility criteria such as having a cross-sectional study design, assessing the general public’s mental health status or sleep problems, medical workers and non-medical workers duringthe COVID-19 pandemic, and using standardized and validated scales for measurement. The keywords: COVID-19 OR SARS-CoV-2 AND Mental health ORPsychological health AND General population OR General public AND sleep AND Impact of Coronavirus disease 2019. A total of 23 articles were selectedafter being assessed. During the period of the COVID-19 pandemic, medical workers were found to have psychological problems such as anxiety, depression, stress, Post-Traumatic Stress Disorder (PTSD), psychological distress, somatization symptoms, suicidal ideation, high risk of severe mental illness, worry, and insomnia. Non-medical workers experienced symptoms of depression. The general public experienced psychological problems: depression, anxiety, stress, bad mood, inability to stop thinking about COVID-19, panic, and experiencing sleep problems such as changing sleep patterns, sleep disturbances, sleep quality, difficulty with sleep initiation, and shortened sleep duration. The COVID-19 pandemic has been associated with psychological problems and sleep disorders for medical workers, non-medical workers, and the general public.